Impact of steel substrate preheating on microstructure and properties of twin-roll cast aluminium-steel clad strips. (2017) - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko
Abstract: Manufacturing of aluminium-steel clad strips by means of twin-roll casting is of a great interest for industrial applications due to shorter production chain in comparison with conventional sheet bonding technologies. The thermal state during the twin-roll casting process has a great influence on the thickness and continuity of the intermetallic phases' layer. This study is dedicated to an analysis of the steel substrate temperature influence on the diffusion bonding at twin-roll casting of the aluminium-steel clad strips. Experiments on twin-roll casting of clad strips of pure aluminium EN AW-1070 and an austenitic stainless steel 1.4301 of a 2.5 mm total thickness with the inline heating of the steel substrate up to 420 °C are performed. The results of the adhesive tensile-strength tests show that the heating of the steel substrate has a positive effect on the bonding strength between the clad strip layers. The investigated procedure of the preheating of steel substrate complements the process parameters of the twin-roll casting for manufacturing of thin clad strips with excellent characteristics.